Children and youth transport in different urban morphological types - Satu-Maaria Sarjala; Anna Broberg; Ari Hynynen (Journal of Transport and Land Use)
As demonstrated in many earlier studies, the qualities of physical environment have great impacts on physical activity (PA) behavior. However, studying individual built-environment variables often produces contradictory effects between studies. To overcome this, we composed multivariate environment types using principal component analysis that takes notice of the inter-correlations between physical-environment variables. To get a realistic view of the places children and adolescents visit in their daily life, we used mapping methodology in which children themselves defined their important places. Based on 16 built-environment variables, six built-environment types were composed around these places.